การพัฒนาทักษะการอ่านสะกดคำพื้นฐานภาษาไทยโดยการเรียนรู้แบบ Active Learning สำหรับนักเรียนชั้นประถมศึกษาปีที่ 6 โรงเรียนบ้านหนองไม้ตายหนองซองแมว ตำบลทุ่งนางโอก อำเภอเมืองยโสธร จังหวัดยโสธร - ศรีภูงา, จิตรานุช; แสนสิ่ง, พีรพงษ์; โทอื้น, วรเชษฐ์ (วารสาร มมร ยศสุนทรปริทรรศน์, 2025)
The present study was conducted with main objectives. The first was to develop and evaluate the efficiency of a Thai vowel learning reading exercise set based on the 80/80 standard criterion. The second was to compare the reading and spelling abilities of Grade 6 students in relation to words containing single vowel sounds, before and after participating in an instructional approach that integrated Active Learning activities with the reading exercise set. The research employed a one-group pre-test-post-test experimental design. The participants were 12 Grade 6 students from Ban Nong MaiTai Nong SongMaew School, located in Thung Nang Oak Subdistrict, Mueang Yasothon District, Yasothon Province. The research instruments comprised three components: lesson plans designed to promote Active Learning, the Thai vowel learning reading exercise set, and a reading and spelling ability test focusing on single vowel sounds. Data were analyzed using  percentage the mean (µ) and standard deviation (σ). Findings revealed that the developed Thai vowel learning reading exercise set achieved an efficiency score of 82.12/81.82, surpassing the set criterion of 80/80. In terms of learning outcomes, the average pretest score was 11.73, while the average posttest score increased to 15.27. The improvement in posttest scores was statistically significant at the .05 level, indicating that the integration of Active Learning activities with the reading exercise set effectively enhanced the students’ ability to read and spell words containing single vowel sounds. These results highlight the potential of combining interactive learning strategies with structured reading materials to improve early literacy skills among young learners. The study not only confirms the effectiveness of the developed materials but also reinforces the value of Active Learning as a pedagogical approach in primary education.